Periodontal and Gingival Health of Pregnant Women in Comparison to Non-Pregnant Women - Butt, Hira; Khan, Nauman; tahir, Fizza; Piracha, Maila Habib (Pakistan Armed Forces Medical Journal, 2022)
Objective: To assess pregnant women's periodontal and gingival health compared to non-pregnant women.Study Design: Cross-sectional comparative study.Place and Duration of the Study: Department of Gynecology, Sharif Medical and Dental College, and Raiwind Polyclinic Lahore (Outreach program of the Sharif Medical and Dental College, from Mar 2019 to Aug 2019.Methodology: The periodontal and gingival health of 44 pregnant and 52 non-pregnant females was evaluated using the community periodontal index of treatment needs and gingival index. Results: A total of 44 pregnant and 52 non-pregnant were evaluated. The periodontal health and pregnancy status were significantly associated (p=0.008). The periodontal health and the trimester of pregnancy were not significantly associated (p=0.787). There was no significant association between the gingival health of the females with the status of pregnancy (p=0.773). Maximum calculus deposition in the oral cavity of pregnant women was during the third trimester (36.4%).Conclusion: The pregnant females had a higher percentage of bleeding gums, while calculus deposition was higher in non-pregnant females. Pregnant females had more periodontal pockets of 4-5 mm, while pocket depths of 6mm or more were seen in non-pregnant females only.